Enantioseparation and determination of orphenadrine in rat plasma and its application to a stereoselective pharmacokinetic study. (9th March 2021) - Liu, Yanru; Ding, Yushan; Song, Yongbo; Guo, Xingjie
Abstract : Chiral separation and stereoselective pharmacokinetics study of orphenadrine enantiomers in rats by HPLC-MS/MS. Abstract : A simple, sensitive, and enantioselective HPLC-MS/MS method has been developed for the determination of orphenadrine (ORP) enantiomers in rat plasma for the first time. The method used diphenhydramine as the internal standard (IS), and plasma samples were extracted by liquid–liquid extraction with satisfactory recovery. Chiral separation of the ORP enantiomers was obtained on a Chiralcel OD-RH column (150 mm × 4.6 mm, 5 μm). The mobile phase consists of acetonitrile–ammonium bicarbonate buffer (30 mM, pH 9.0) (80 : 20, v/v). Sufficient resolution ( R s = 3.562) was achieved in a short analysis time (7 min). The multiple reaction monitoring (MRM) mode was used for the detection of ORP enantiomers and IS. The transitions of m / z 270.0 → 181.1 and 256.2 → 167.1 were chosen for monitoring the ORP enantiomers and IS, respectively. Linearity was confirmed in the range of 0.1–50.0 ng mL −1 with the lower limit of quantification of 0.1 ng mL −1 for both ORP enantiomers in plasma. After validation, the method was applied to the enantioselective pharmacokinetic study of ORP enantiomers in rat plasma following oral administration of 10 mg kg −1 racemic ORP. Significant differences ( P < 0.05) of ORP enantiomers were observed in pharmacokinetic parameters including C max, AUC, t 1/2, CL, V d, MRT, and VRT, which indicated that enantioselective pharmacokinetic behavior of ORP enantiomers was present in rats.